Psychological Adaptive Mechanism Maturity, Age, and Depression Symptoms in Advanced-Stage Cancer Patients - Beresford, Thomas; Teschke, Patricia U.; Hipp, Daniel; Ronan, Patrick J. (Frontiers in Psychology, 2021)
Background: Previously, we reported that the maturity of Psychological Adaptive Mechanism (PAM; alternatively ego defense mechanism) endorsement, but not depression symptom severity, predicted 5-year survival rates in adult cancer patients. That study controlled for age as a significant variable. In this investigation, we hypothesized that greater PAM maturity would correlate significantly with age and with fewer depression symptoms in a larger sample. Methods: In this cross-section study, adult cancer outpatients (N=293) completed the Defense Style Questionnaire (DSQ), the Beck Depression Inventory (BDI), and provided additional clinical data. Spearman’s correlation and multiple regression modeling provided statistical tests of the study hypotheses. Results: Contrary to our hypothesis, DSQ PAM maturity endorsement did not correlate significantly with increasing age. Greater PAM maturity ratio on the DSQ (p<0.0001) and current antidepressant use (p<0.05), however, both provided inverse associations with total BDI symptom frequency (p<0.01). Age was inversely associated with BDI mood (p<0.0001) and somatic scores (p<0.04). Items that worsened BDI symptom frequency included self-reported mood-altering anti-cancer medications and any psychiatric history. Cancer stage, time since diagnosis, and chemotherapy treatment did not correlate with DSQ or BDI scores. Multiple regression analysis found that the correlated items accounted for 17.2% of the variance in mood symptoms and 4.9% in somatic symptoms. Specifically, adaptive maturity and age, associated with fewer depression symptoms, while cancer medications affecting mood, and a previous psychiatric history each predicted higher frequency of depression scores. Conclusion: The results suggest that PAM maturity predicts fewer depression symptoms while younger age predicts more depression symptoms in this clinical sample. Centrally acting cancer medications, any history of psychiatric disorder, and, possibly antidepressant medications, increased depression symptom frequencies. Further research should target factors that improve PAM maturity as a potential treatment target, especially in younger age groups.